2017
DOI: 10.1186/s12944-017-0501-y
|View full text |Cite
|
Sign up to set email alerts
|

Sake lees extract improves hepatic lipid accumulation in high fat diet-fed mice

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is increasing worldwide as one of the leading causes of chronic liver disease. Sake lees (SL) are secondary products of sake manufacturing and are considered to have beneficial effects on human health. To investigate these effects, we used high fat diet (HFD)-fed mice treated with or without the SL extract.MethodMice were the HFD ad libitum for 8 weeks and were administered 500 μL of distilled water with or without the SL extract (350 mg/mL) by a feeding needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Collectively, hepatic lipid accumulation can cause hepatic insulin resistance through multiple mechanisms (Konstantynowicz et al, 2011). Therefore, it is widely accepted that suppression of hepatic lipid accumulation is a promising approach for the therapy of hepatic insulin resistance (Konstantynowicz et al, 2011; Mohamed and Jornayvaz, 2013; Kubo et al, 2017).…”
Section: Mechanism Of Hepatic Insulin Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, hepatic lipid accumulation can cause hepatic insulin resistance through multiple mechanisms (Konstantynowicz et al, 2011). Therefore, it is widely accepted that suppression of hepatic lipid accumulation is a promising approach for the therapy of hepatic insulin resistance (Konstantynowicz et al, 2011; Mohamed and Jornayvaz, 2013; Kubo et al, 2017).…”
Section: Mechanism Of Hepatic Insulin Resistancementioning
confidence: 99%
“…Free fatty acids are by-products of fat metabolism in adipose tissues. The cause–effect relationship between hepatic free fatty acid accumulation and hepatic insulin resistance has been well described (Liu et al, 2015; Kubo et al, 2017).…”
Section: What Are Fatty Acids?mentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have revealed that sake lees have functional properties, such as inhibiting cholesterol increase, lowering blood pressure, and inhibiting liver damage in mice. Moreover, clinical studies have reported improved environmental conditions in human intestines [9,10]. However, the mechanisms of action of sake lees and the roles of their specific components are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sake lees sake-kasu, sake cake is a byproduct of sake and is used as a bed for pickling kasu-duke , a material of soup and drink kasu-jiru and amazake , and a source for Japanese spirits and vinegar kasutori-shochu and kasu-zu . Sake lees has been reported to improve hepatic lipid accumulation 13 and has been shown to contain GlcCer with a fungi-specific sphingoid base 14 .…”
mentioning
confidence: 99%